A History of Catholic Antisemitism - Michael, R. author. aut Link
IX, 282 p.
Keywords: Moving from the Catholic Church's pagan origins, through the Roman era, middle ages, and Reformation to the present, Robert Michael here provides a definitive history of Catholic antisemitism.